Management of Temporary Shelters in Brazil: challenges and Recommendations from Planning to Deactivation - Carbonari, Luana Toralles; Costa, Fernando Guilherme da; Vieira, Ana Claudia da Silva; Toralles, Berenice Martins (National Journal of City Management, 2025)
Objective – This paper analyzes the challenges faced in the management of temporary shelters in Brazil, focusing on the humanitarian crises in Roraima (Venezuelan migration flow, 2018–2023) and Rio Grande do Sul (floods, 2024). Methodology – The study adopts a qualitative and comparative approach, based on documentary analysis of official reports, open data platforms, and scientific literature on disaster management and humanitarian response. Originality/Relevance – The research fills a gap in the literature by critically systematizing the structural and operational obstacles in the management of temporary shelters in distinct but recurring Brazilian contexts. Results – Recurring failures were identified in the four stages of the shelter management cycle (planning, activation, operationalization, and deactivation), worsened by the absence of standardized national guidelines, lack of interinstitutional coordination, and scarcity of local data. Theoretical/Methodological Contributions – The article proposes an integrated management model with sectoral protocols, a national database of suitable shelter locations, interagency communication plans, and the professionalization of municipal and state civil defense, based on international standards such as the Sphere Handbook. Social and Environmental Contributions – By outlining paths to strengthen territorial resilience and ensure more dignified and effective shelters, the study contributes to the development of more equitable, safe, and sustainable public policies for disaster response in Brazil.